STRATEGI MENINGKATKAN DAYA SAING PADA KLINIK KECANTIKAN dr. Reni G - Lusi Zafrina, lusizafrina (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
Moving in the beauty industry is one of the industrial fields that will remain prospective and as the right step in investing and answering an increasingly modern lifestyle where maintaining appearance is the main thing for some people. Beauty Clinic dr. Reni G is one of the beauty clinics that has been established for more than ten years but in its development has experienced a decline in sales, although it has carried out various strategies with the application of a fairly interesting collaboration  concept. This study initiated the Beauty Clinic dr. Reni G to make continuous improvements as outlined in the Canva s Business Modelas the results of data persentase tassumption responden with a value of 88% to increase competitiveness.  Business Model Canvas provides convenience and flexibility for business people in evaluating the wheels of their business periodically through its nine elements. The results of the study showed that the Beauty Clinic dr. Reni G implemented the Business Model Canvas by creating value proposaltion not only providing friendly, trustworthy, honest, quality services at affordable prices but beauty dr. Reni G is here to educate and care for the community.